"Teenagers from outer space" - Graeff, Tom, 1929-1970; Tom Graeff Productions; Cinetel Films ([Los Angeles, CA] : Tom Graeff Productions, 1959)
A strange flying saucer lands in the desert near Hollywood, bringing a deadly menace to Earth: a mischievous gang of teenagers from outer space!
David Love, Dawn Anderson, Bryan Grant, Harvey B. Dunn, Tom Lockyear.
Photography, editing and sound by Tom Graeff.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 28, 2015).
Keywords: Human-alien encounters -- Drama; Life on other planets -- Drama; Teenagers -- Sexual behavior -- Drama; Teenagers -- Drama; Science fiction films; B films; Feature films; Internet videos; Streaming video